2019
DOI: 10.1093/infdis/jiz423
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of C-Type Lectin REG3α and Gut Damage in People With Human Immunodeficiency Virus

Abstract: Background Regenerating islet-derived protein 3α (REG3α) is an antimicrobial peptide secreted by intestinal Paneth cells. Circulating REG3α has been identified as a gut damage marker in inflammatory bowel diseases. People living with human immunodeficiency virus (PWH) on antiretroviral therapy (ART) present with an abnormal intestinal landscape leading to microbial translocation, persistent inflammation, and development of non-AIDS comorbidities. Herein, we assessed REG3α as a marker of gut d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 50 publications
(78 citation statements)
references
References 45 publications
(78 reference statements)
5
68
1
Order By: Relevance
“…REG3α is an antimicrobial peptide secreted by intestinal Paneth cells into the gut lumen and upon gut damage, translocates into the blood (14). We observed that these two gut damage markers were correlated with HIV disease progression, microbial translocation and immune activation in PLWH (14). These findings point to the leaky gut as a significant contributor to chronic inflammation and non-AIDS comorbidities in PLWH.…”
Section: Leaky Gut and Dysbiosis In Plwhmentioning
confidence: 66%
See 3 more Smart Citations
“…REG3α is an antimicrobial peptide secreted by intestinal Paneth cells into the gut lumen and upon gut damage, translocates into the blood (14). We observed that these two gut damage markers were correlated with HIV disease progression, microbial translocation and immune activation in PLWH (14). These findings point to the leaky gut as a significant contributor to chronic inflammation and non-AIDS comorbidities in PLWH.…”
Section: Leaky Gut and Dysbiosis In Plwhmentioning
confidence: 66%
“…I-FABP, an intracellular protein constitutively expressed in enterocytes, is released upon cell death and subsequently detected in the blood (96,97). REG3α is an antimicrobial peptide secreted by intestinal Paneth cells into the gut lumen and upon gut damage, translocates into the blood (14). We observed that these two gut damage markers were correlated with HIV disease progression, microbial translocation and immune activation in PLWH (14).…”
Section: Leaky Gut and Dysbiosis In Plwhmentioning
confidence: 73%
See 2 more Smart Citations
“…Circulating intestinal fatty acid binding protein (I-FABP) and regenerating islet-derived protein-3α (REG3α) are two validated gut damage markers in PLWH [23,24]. I-FABP, an intracellular protein constitutively expressed in enterocytes, is released upon cell death and subsequently detected in the blood in inflammatory bowel diseases (IBD) and HIV infection [25,26].…”
Section: (1→3)-β-d-glucan (Bdg) Is a Major Component Of Most Fungal Cmentioning
confidence: 99%